INVESTIGATION OF EFFECTIVENESS OF PURIFICATION THE ROKACH RIVER OF GOSTOMEL SETTLEMENT FROM ANTROPOGENIC POLLUTION - Матвєєва, О. Л.; Тихорська, А. П. (Science-based technologies, 2014)
The most available source of fresh water on the Earth is the river flow. Due to excessive human pressure a lot of small rivers, among witch The Rokach is also, are loosing its ability to self-purification. In this article the expediency of using of the biopond for cleaning the Rokach river of Gostomel settlement from antropogenic pollution is described. Cleaning mechanisms of polluted water are evaluated. The way of intensification of the biopond is theoretically grounded and experimentally proved by introducing of Chlorella and Scenedesmus algae and higher aquatic plants like as Cane, Cattail narrow-leaved and broadleaf, Potamogeton crispus and duckweed (Lemna minor) in it. This review emphasizes the effect of environmental factors (the temperature and the day length) on the water treatment effectiveness.